2009
DOI: 10.1038/jp.2008.188
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of NICU professionals regarding feeding blood-tinged colostrum or milk

Abstract: Objective: Mothers of neonatal intensive care unit (NICU) patients sometimes bring expressed milk that is blood tinged to the NICU. In certain instances, the blood contamination appears minimal, whereas in others, the milk is quite dark pink. We have observed inconsistencies in practice regarding whether or not to feed blood-tinged colostrum or milk to NICU patients. We know of no evidence that establishes best practice in this area, and thus we sought to determine attitudes of NICU professionals on which to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We read with interest the only available papers on blood-tinged milk by Phelps et al 1,2 Although benefits of human milk (HM) to both healthy and high-risk infants are well known, 3 it is a common belief that blood-tinged milk may worsen gastrointestinal tolerance and, possibly, lead to unnecessary investigations for gastrointestinal bleeding or necrotizing enterocolitis. In their first work, Phelps et al 1 showed that the amount of blood necessary to tinge milk is very little, with a ratio of 1:10 000 between parts of red blood cells and milk to tinge it faintly pink, a ratio of 1:1000 to tinge it pink and of 1:100 to tinge it red.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the only available papers on blood-tinged milk by Phelps et al 1,2 Although benefits of human milk (HM) to both healthy and high-risk infants are well known, 3 it is a common belief that blood-tinged milk may worsen gastrointestinal tolerance and, possibly, lead to unnecessary investigations for gastrointestinal bleeding or necrotizing enterocolitis. In their first work, Phelps et al 1 showed that the amount of blood necessary to tinge milk is very little, with a ratio of 1:10 000 between parts of red blood cells and milk to tinge it faintly pink, a ratio of 1:1000 to tinge it pink and of 1:100 to tinge it red.…”
mentioning
confidence: 99%
“…In their first work, Phelps et al 1 showed that the amount of blood necessary to tinge milk is very little, with a ratio of 1:10 000 between parts of red blood cells and milk to tinge it faintly pink, a ratio of 1:1000 to tinge it pink and of 1:100 to tinge it red. They showed that 75% of neonatal intensive care unit professionals from 18 hospitals in the western United States would discard milk if pink, raising to 98% if red.…”
mentioning
confidence: 99%
“…Very small amounts of mother's blood can result in pink or even red expressed mother's milk (1). In the NICUs of our healthcare system, and we suspect in many other NICUs as well, blood-tinged mother's milk is not fed, but is discarded.…”
mentioning
confidence: 99%
“…In the February 2009 issue 1 we reported results of an e-survey of neonatal intensive care unit (NICU) professionals at Intermountain Healthcare regarding feeding NICU patients blood-tinged expressed mother's milk. We received 421 survey responses; 7% of respondents would discard the milk shown as #1 (faintly red breast milk), 75% would discard milk #2 and 98% would discard milk #3 (very red sample) (see Figure 1 in Phelps et al 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation